Recurrent Aphthous Stomatitis: Diagnosis and Management in Primary Care - Jillian Hudson (Journal of Patient-Centered Research and Reviews, 2014)
Recurrent aphthous stomatitis (canker sores) is a very common oral condition that remains incompletely understood. Presentation has been well-classified into minor, major or herpetiform subcategories based on clinical features, but exact etiology is unknown. Because etiology is unclear, treatments are primarily empiric and aimed at symptom reduction rather than prevention or cure. However, there are several methods, both topical and systemic, that can be easily and affordably utilized in the primary care setting.